1952
DOI: 10.1084/jem.95.5.473
|View full text |Cite
|
Sign up to set email alerts
|

Elicitation of Delayed Allergic Skin Reactions With Haptens: The Dependence of Elicitation on Hapten Combination With Protein

Abstract: Allergic skin reactions of the delayed type may be conveniently considered to involve two distinct processes: first, induction of the sensitized state, and second, elicitation of the allergic reaction in the sensitized individual. With regard to the induction of sensitization, it is generally believed that low molecular weight substances (haptens) can function effectively in this respect if they combine in vivo with tissue constituents, presumably proteins. This belief, which had long been reasonably maintaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
1

Year Published

1955
1955
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(43 citation statements)
references
References 20 publications
1
41
0
1
Order By: Relevance
“…3, ear thickness in the mock-infused group increased by 3.5-fold compared with that of the unchallenged opposite ear, but infused MSCs completely suppressed ear swelling. The immune response for DTH is known to be mediated predominantly by T cells (35). Consistent with this notion, we found that apoptotic T cells were significantly increased in the draining LNs, and the infiltration of T cells in the inflamed site was markedly reduced in MSC-treated mice during the DTH response.…”
Section: Discussionsupporting
confidence: 86%
“…3, ear thickness in the mock-infused group increased by 3.5-fold compared with that of the unchallenged opposite ear, but infused MSCs completely suppressed ear swelling. The immune response for DTH is known to be mediated predominantly by T cells (35). Consistent with this notion, we found that apoptotic T cells were significantly increased in the draining LNs, and the infiltration of T cells in the inflamed site was markedly reduced in MSC-treated mice during the DTH response.…”
Section: Discussionsupporting
confidence: 86%
“…The importance of this route has been further emphasized by studies on sensitization to simple chemicals (13,14), wherein topical application in off of such substances as picryl chloride induces a delayed type of allergy. Also, when antigen-antibody complex is injected ~ia the intradermal route, greater delayed sensitivity is induced than when it is injected da the intraperitoneal, subcutaneous, or intramuscular route (1).…”
Section: Discussionmentioning
confidence: 99%
“…3 is a T cell-mediated immune response of the skin in sensitized individuals to subsequent contact with the sensitizing hapten (1,2). During sensitization for CHS, hapten-presenting Langerhans cells (hpLC) migrate to the skin-draining lymph nodes and prime the hapten-specific T cells, which mediate the response to hapten challenge (3)(4)(5).…”
Section: Ontact Hypersensitivity (Chs)mentioning
confidence: 99%